Spending on special educational needs in England: Something has to change - Luke Sibieta; Darcey Snape (Institute for Fiscal Studies (IFS), 2024)
The special educational needs and disabilities (SEND) system in England has faced unprecedented pressure over the past decade, and without substantial reform it will likely become unmanageable for local authorities over the coming years. Fundamentally, this is due to the rocketing number of children and young people with education, health and care plans (EHCPs). Children with EHCPs are those with the highest needs and local authorities are statutorily obligated to cover the costs of provision set out in EHCPs. The reasons behind this rise in EHCPs are complex, but potential explanations include increased severity of needs, expanded recognition and diagnosis of needs, and stronger incentives to seek statutory provision.
Keywords: 330; Education and skills; Disability; Education; Government spending; Local government finance; Schools